Сюжет з кентавром на фракійській збруї з кургану Огуз - Фіалко, О.Є. (Археологія, 1993)
На основі аналізу фрагментованого срібного нащічника з кургану Огуз, реконструюється зображена на ньому сцена та визначаються її дійові особи. В комплексе конской узды из скифского кургана Огуз есть гарнитур, в состав которого входит пара серебряных с позолотой нащечнйков с изображением трех фигур. Из-за плохой сохранности блях, сюжет их изображения истолковывался неверно. Используя один из первых фотоснимков нащечника, автор «восстанавливает» изображенную на нем сцену и, привлекая известные археологические параллели и нарративные источники, приходит к выводу, что нащечники были украшены сюжетом из жизни Ахилла. В частности речь идет об изображении кентавра Хирона и его жены Хариклы, которые держат на руках маленького Ахилла в момент отъезда в путешествие аргонавтов, среди которых был и отец Ахилла — Пелей. The bridle complex from the Scythian barrow Oguz contains the couple of the cheeck- plates made of gilded silver which displays the three figures. Because of poor preservation of the plates the subject of their picture was interpreted incorrectly. Using the one of the first photographs of the cheeck-plates the author «restores» the displayed scene and applying the well-known archaeological analogies and narrative sources comes to the conclusion that the cheeck-plates were decorated by the subject from the life of Achilles, in particular, by the images of Centaur Khyrones and his wife Kharicla. At the cheeck-plates they are displayed with the little Achilles in the arms at the monent of seeing off the Argonauts among whom the Achilles’ father — Peleius — was.